Formula for predicting ground settlement induced by tunnelling based on Gaussian function. (September 2020) - Lu, Dechun; Lin, Qingtao; Tian, Yu; Du, Xiuli; Gong, Qiuming
Highlights: A formula for the maximum ground settlement induced by tunnelling is proposed. A method is developed to predict the settlement at any position above the tunnel. The application of the developed method is demonstrated by a field project case. Rationality of the suggested methods is checked by field projects and model tests. Abstract: A formula for the variation of the maximum ground settlement with the depth above a tunnel is proposed based on data from 25 field project cases and 10 model test cases. The Gaussian function is developed by introducing the proposed formula and an existing formula for settlement trough width coefficient, to predict the settlement above the tunnel in the transverse section. There are two parameters, n and k, in the developed Gaussian function, and determination methods of the new parameter n are provided for clay strata and sand strata, respectively. The application method of the developed Gaussian function is demonstrated by a field project case. Finally, applicability of the formula for the maximum ground settlement and the developed Gaussian function are validated by 12 field project cases and 9 tunnelling model test cases conducted by the authors.